Visualizing communication structures in science classrooms: Tracing cumulativity in teacher‐led whole class discussions. Issue 8 (8th August 2013) - Lehesvuori, Sami; Viiri, Jouni; Rasku‐Puttonen, Helena; Moate, Josephine; Helaakoski, Jussi
Abstract Teacher‐led whole class discussions are essential when it comes to guiding students' construction of knowledge, and recent studies on teaching and learning emphasize the need for more student‐centered teaching methods. In previous studies, the extent to which different types of communication take place in the classroom have been extensively reported by means of lists, tables, and charts, yet these studies have not included overviews of how talk develops and progresses over time. This study addresses this aspect by presenting how different communicative approaches constitute a specific, cumulative communication structure. Within this structure, the role and temporal considerations of a dialogic approach to teaching are examined within a teaching sequence on the topic of electrical power and energy. The case data were analyzed on multiple levels. First, teaching sequences were presented graphically to provide a broader picture of the communicational orientation of the overall lesson. Second, a detailed analysis of dialogic interactions was executed to understand the quality and role of these interactions on a broader communicational level. This multilevel analysis provides insights into the different purposes and quality of dialogic implementation in terms of the cumulative and meaningful learning of science. Implications for teaching and teacher education and educational research are also discussed. © 2013 Wiley Periodicals, Inc. J Res Sci Teach 50: 912–939, 2013